Breaking Barriers: The Design and Development of an Assistive Technology Web App for Older Latinos with Disabilities in Daily Activities - Elsa M. Orellano-Colón; Adriana I. Ramos-Marichal; Valeria R. González-Crespo; Bianca N. Zeballos-Hernández; Kenneth N. Ruiz-Márquez; Abiel Roche-Lima; Joan M. Adorno-Mercado; Norman A. Laborde-Torres; Joshua G. Berríos-Llopart; Angely M. Cruz-Ramos; Dana V. Montenegro; Carmen E. Lamoutte; et al. (Technologies)
Latinos are among the populations who are the least likely to use assistive technology (AT) despite being a population with a high prevalence of functional disabilities (FDs). We aimed to create and test the usability of an AT web app for independent-living older adults with FDs. In Phase I, we created the web app’s content guided by the Optimized Honeycomb Model and considered the AT needs and FDs of older Puerto Ricans found in our previous studies. In Phase II, we design the web application by adopting a Lean UX process and design heuristics for older adults. In Phase III, we conducted usability testing using focus groups and individual interviews with 14 older adults, interpreted through a directed content analysis. The Mi Guía de Asistencia Tecnológica (MGAT) was developed with ninety-four AT devices in eight areas of daily activities. The MGAT provides comprehensive information on AT, including photos and videos of older adults using AT. Participants reported that the MGAT was usable, accessible, credible, desirable, useful, and valuable in increasing their knowledge of AT. These findings are a foundation for developing efficient AT information strategies using such technology as a first step to improving AT adoption among older adults.